The recombinant collagen-like protein as animal-based collagen substitution: a qualitative study - Duasa, Jarita; Mohamed Noor, Siti Fatimah; Mohd Thas Thaker, Mohamed Asmy; Rahman, Maya Puspa (Universiti Teknologi Mara (UiTM), 2020)
Collagen has been used widely in food, pharmaceutical, cosmeceutical, biomedical, tissue engineering and film industries. The surge concern on the halal issues of Collagen, which mainly originates from porcine or pork as well as bovine, leads to the development of the recombinant collagen-like protein as an alternative of animal-based Collagen. It can be a substitution for halal and vegetarian industries. The aim of this study is, therefore, to discuss on the issue of halal Collagen and the experts' opinion on the new technology of the recombinant collagen-like protein to substitute non-halal and doubtful sources of Collagen. The study is carried out by holding an in-depth interview with the experts who are from various areas of expertise and different academic background. These experts concur similar definition of Collagen. Even though they had different opinions on the suitability of bacteria-based Collagen to be used in production, they mutually agreed that the bacteria-based Collagen has a massive prospect in Malaysian industries. Thus, companies should produce final products that use bacteria-based Collagen as it may tempt a lot of consumers who concern about the resources used in the product produced. The experts also agreed that halal certification on the alternative source of Collagen could boost confidence among consumers on the final products produced.